Oral cancer cells secrete stress neurotransmitter and proliferate in response to tobacco carcinogen NNK - Verza, Flávia Alves [UNESP]; Santos-Sousa, Ana Lívia [UNESP]; Oliveira, Sandra Helena Penha [UNESP]; Bernabé, Daniel Galera [UNESP] (Bioscientifica, 2025)
Purpose: Although there is a growing body of evidence showing the effects of stress-related catecholamines on oral cancer progression, to date there are no studies that have investigated whether oral squamous cell carcinoma (OSCC) cells can produce these hormones and whether this phenomenon is modulated by tobacco-related nitrosamines. Methods: In this study, we investigated whether keratinocytes (HaCaT) and OSCC-derived cell lines (SSC9 and SCC25) can secrete the neurotransmitter norepinephrine, as well as the effects of the tobacco carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) on norepinephrine secretion and OSCC proliferation. Results: Supernatant from the HaCaT, SCC9 and SCC25 cells showed higher norepinephrine levels (6-, 14.9- and 15.1-fold higher, respectively) compared to the culture medium without cells. When the cells were stimulated with NNK, a tobacco-specific carcinogen, there was an increase in the levels of norepinephrine secretion by HaCaT and SCC25 cells but not by SCC9 cells. NNK (10 μM) induced cell proliferation in the HaCaT, SCC9 and SCC25 cell lines, and these effects were totally inhibited by blocking β-adrenergic receptors with propranolol. The NNK-induced OSCC cell proliferation was furthermore dependent on the activation of nicotinic acetylcholine receptors α4 (nAChR-α4) (completely in SCC9 cells and partially in SCC25 cells) but not on the activation of nAChR-α7. Inhibition of the β-adrenergic receptors, nAChR-α4 and nAChR-α7 did not block NNK-induced HaCaT proliferation. Conclusion: Our findings suggest that oral cancer cells secrete the neurotransmitter norepinephrine and that the tobacco nitrosamine NNK promotes increased cell proliferation through a stress-related cellular adrenergic pathway.